Identification Charts for Planetary Nebulae - Pik Sin The (Journal of Mathematical and Fundamental Sciences, 1964)
Abstract. At Dr. L. Perek's request, identification charts for 12 known planetary nebulae, of which the locations were not certain, are given. Ichtisar. Atas permintaan Dr. L. Perek, peta pengenal untuk 12 kabut planit jang letaknja diragukan, disadjikan dalam tulisan ini.